Thelma & Louise [videorecording (DVD)] - Scott, Ridley; Scott, Ridley; Khouri, Callie; Sarandon, Susan, 1946-; Davis, Geena; Keitel, Harvey; Madsen, Michael; McDonald, Christopher, 1955-; Tobolowsky, Stephen, 1951-; Pitt, Brad, 1963-; Carhart, Timothy, 1953-; Jenney, Lucinda; et al. (MGM Home Entertainment ; Distributed by Twentieth Century Fox Home Entertainment, 2010)
Two women friends leave their partners for a short trip, but an unexpected incident turns them into fugitives from the law.